2023
DOI: 10.3390/polym15040870
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater from the Arenga Starch Industry as a Potential Medium for Bacterial Cellulose and Cellulose Acetate Production

Abstract: Wastewater from the Arenga starch industry (WWAS) contains a high chemical oxygen demand (COD) concentration, so it has to be treated before being discharged into water bodies. Therefore, the purpose of this study was to utilize WWAS as a medium for bacterial cellulose (BC) and cellulose acetate (CA) production. This study consisted of the production of BC through fermentation and the production of CA through acetylation. Fermentation was conducted under static batch conditions with various initial pHs and suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
0
0
Order By: Relevance
“…This indicated that most of the hydroxyl groups (O-H) originating from cellulose were replaced by acetate groups [24]. The lack of absorption in the 1840 cm -1 region in Figure 1(b) indicated that the product was free from acetic acid [25]. The success of the acetylation reaction was also proven in the formation of a carbonyl group (C=O) at an intensity of 1753 cm -1 and an acetyl group (C-O) at a power of 1043 cm -1 with a fairly high level of peak state.…”
Section: Electrode Fabricationmentioning
confidence: 97%
“…This indicated that most of the hydroxyl groups (O-H) originating from cellulose were replaced by acetate groups [24]. The lack of absorption in the 1840 cm -1 region in Figure 1(b) indicated that the product was free from acetic acid [25]. The success of the acetylation reaction was also proven in the formation of a carbonyl group (C=O) at an intensity of 1753 cm -1 and an acetyl group (C-O) at a power of 1043 cm -1 with a fairly high level of peak state.…”
Section: Electrode Fabricationmentioning
confidence: 97%